Iterated Elimination of Dominated Strategies in a Bertrand-Edgeworth Model - Borgers, Tilman (Review of Economic Studies, 1992)
The author considers a Bertrand-Edgeworth model of price competition. Firms have identical and constant marginal costs and finite exogenous capacities. Firms choose prices. The author's interest is in the set of those prices which are left over after the iterated elimination of dominated strategies. The author shows that in two circumstances this set will be close to the set containing only the market-clearing (Walrasian) price: (1) if any n - 1 out of n firms assumed to be in the market have sufficient capacity to cover demand at marginal costs; (2) if any given total capacity is owned by a very large number of very small firms. Copyright 1992 by The Review of Economic Studies Limited.